Service Culture: Concept And Measurement - Robiansyah Robiansyah (Faculty of Economics and Business Mulawarman University, 2017)
This paper aims to review several studies on service culture in term of concept and measurement aspect. Conceptual review is urgent to guide scholars develop and choose the best concept which is represented the phenomenon in human resource management context. Meanwhile, for empirical studies, it is important for researcher using appropriate measurement in its questionnaire development. As result, this paper suggest a set of indicators to measure service culture in hotel industry. Keywords: Service culture, conceptualizing, measurement, and hotel industry.